Vecāku līdzestība Gastroezofageālā refluksa slimības pacientu aprūpē - Rozenšteina, Jana (Latvijas Universitāte, 2020)
Bakalaura darba tēma – Vecāku līdzestība Gastroezofageālā refluksa slimības pacientu aprūpē. Tēmas aktualitāti nosaka, ka gastroezofageālās refluksa slimība ir izplatīta visās bērnu vecuma grupās, un vecāku līdzestība ir svarīgs priekšnoteikums pacientu dzīves kvalitātes uz-labošanai. Darba mērķis ir noskaidrot vecāku līdzestību gastroezofageālā refluksa slimības pacientu aprūpē. Pētījuma hipotēze – Vecāki ir līdzestīgi Gastroezofageāla refluksa slimības pacientu ap-rūpē. Pētniecības metode – kvantitatīvs Pētniecības instruments – aptaujas anketa Secinājumi – Pareizi veicot pacientu piederīgo izglītošanu iespējams panākt labus rezul-tātus vecāku līdzestībā. Līdzestība veicina pacienta dzīves kvalitātes uzlabošanos un novērš slimības progresēšanas iespējas. Pētījumā izvirzītā hipotēze apstiprinājās – vecāki ir līdzestīgi gastroezofageāla refluksa slimības pacientu aprūpē.

Subject of the work - Parental Involvement in the Care of Patients with Gastroesopha-geal Reflux Disease. Relevance of the subject is determined by prevalence of gastroesophageal reflux disease in children of all ages. Parental compliance in managing disease plays a major role in impro-ving quality of life of the young patients. The aim of the work is to establish the level of parental involvement and compliance in management of the care of the child with gastroesophageal reflux disease. Hypothesis of the work- parents tend to be involved and compliant in the care manage-ment of their children with gastroesophageal reflux disease. Research method- quantitative survey Research methodology – questionnaire Conclusions- It is possible to achieve good results in parental compliance, by providing patient’s family with good education in disease management. Good parental compliance im-proves child’s quality of life and decreases chances of disease progression. The raised hypothesis outcome was positive, parents are compliant in management their children’s gas-troesophageal reflux disease.
Parental Involvement in the Care of Patients with Gastroesophageal Reflux Disease
Keywords: Medicīna; gastroezofageālā refluksa slimība; pacientu aprūpe; vecāku līdzestība; māszinības